Some consequences of Wiesend’s higher dimensional class field theory - Schmidt, Alexander (Mathematische Zeitschrift, 2007)
We use a result of G. Wiesend to establish the relation between the integral singular homology in degree zero and the abelianized tame fundamental group of a regular, connected scheme of finite type over Spec(Z).
Der Artikel bezieht sich inhaltlich auf "Class field theory for arithmetic schemes" von G. Wiesend, im gleichen Heft erschienen
Gesehen am 04.05.2018